PENGARUH KECANGGIHAN TEKNOLOGI INFORMASI DAN PENGETAHUAN AKUNTANSI TERHADAP EFEKTIVITAS SISTEM INFORMASI AKUNTANSI PADA PT. PLN (PERSERO) UP3 BANDA ACEH - Syawalina, Cut Fitrika; Purnamasari, Desy; Ananda, Gebrina Rizki (Prodi Perbankan Syariah Fakultas Agama Islam Universitas Muhammadiyah Aceh, 2023)
This research aims to test and analyze the influence of sophisticated information technology and accounting knowledge on the effectiveness of accounting information systems at PT. PLN (Persero) UP3 Banda Aceh. In this research, the intended population is all employees of PT. PLN (Persero) UP3 Banda Aceh has 65 employees. Determining the sample size uses census techniques where the entire population will be used as the sample. The analysis technique used is Multiple Linear Regression Analysis. The research results show that Sophistication of Information Technology and Accounting Knowledge simultaneously influence AIS effectiveness. Sophistication of Information Technology partially influences AIS effectiveness and Accounting knowledge partially influences AIS effectiveness.